Ectopic expression of the male BmDSX affects formation of the chitin plate in female Bombyx mori. Issue 3 (13th January 2014) - Duan, Jianping; Xu, Hanfu; Ma, Shangyuan; Guo, Huizheng; Wang, Feng; Zhang, Liying; Zha, Xingfu; Zhao, Ping; Xia, Qingyou
SUMMARY Mating structures are involved in successful copulation, intromission, and/or insemination. These structures enable tight coupling between external genitalia of two sexes. During Bombyx mori copulation, the double harpagones in the external genitalia of males clasp the female chitin plate, which is derived from the larval eighth abdominal segment; abnormal development of the female chitin plate affects copulation. We report that ERK phosphorylation (p‐ERK) and expression of Abdominal‐B (Abd‐B) in the posterior abdomen of the female adult is lower than in the male. Ectopic expression of the male‐specific spliced form of B. mori doublesex (BmdsxM) in females, however, up‐regulates Abd‐B and spitz (spi) expression, increasing EGFR signaling activity, and thus forming an abnormal chitin plate and reduced female copulation. These findings indicate that Bmdsx affects the development of the eighth abdominal segment by regulating the activity of EGFR signaling and the expression of Abd‐B, resulting in an extra eighth abdominal segment (A8) in males versus the loss of this segment in adult females. Mol. Reprod. Dev. 2014. © 2013 Wiley Periodicals, Inc.